Smartphone-operated affordable PCR thermal cycler for the detection of antimicrobial resistant bacterial genes. - Sanam Pudasaini; Garima Thapa; Bishnu P Marasini; Basant Giri (PLOS Global Public Health, 2023)
Antimicrobial resistance (AMR) is a global public health threat. Surveillance of AMR requires affordable, rapid, and user-friendly diagnostic methods. Our aim was to develop a low-cost thermocycler to perform polymerase chain reaction (PCR). We developed a smartphone-operated PCR thermal cycler using locally available recycled materials. The thermal cycler was used for the amplification for three bacterial genes-bla-TEM, bla-CTXM and 16s rRNA in human urine samples. The performance of custom-built thermal cycler was compared with commercial thermal cycler. The thermal cycler was portable (<1kg weight), required 12 V power supply, 25 μL of solution, and cost only USD50.0. Temperature and time conditions were instructed using a custom-built smartphone application. The ramping rate of was 0.23°C for heating and 0.43°C for cooling. The reported temperatures were within ± 0.5°C of set temperature. The human urine samples were highly resistance and multi-resistant. Nearly 46% (n = 54) E. coli isolates were positive in ESBL screening test. The custom-built thermocycler was able to accurately predict the presence of bla-TEM, bla-CTXM genes, and 16s rRNA (n = 6). We developed and demonstrated a portable, low-cost, easy-to-use, and smartphone-operated PCR thermal cycler. Since it is portable, it can be used in remote location and field settings, including places without stable power supply. The use of the thermal cycler system can be extended, beyond the detection of AMR genes, e.g., in clinical diagnosis, genetics, forensic analysis, and environmental protection.